Determinants of Entrepreneurial Inclination among Management Students - Gwachha , Anju; Dhital , Rakshya (Khwopa Journal, 2025)
Entrepreneurship is the pressing issues at present for creating employment opportunities and to solve economic problems by applying creative and innovative skills of graduate students. This study aimed to examine the effect of entrepreneurial education and entrepreneurship support programs offered by colleges such as entrepreneurial curricula, course content, role models, and the image of entrepreneurship on the development of entrepreneurial inclination among management students. Descriptive and correlational research design has been used in this study. Data were collected from 175 management students from different colleges affiliated under Tribhuvan University, with 155 valid response. Descriptive statistics, correlation coefficients and multiple regression analysis were used to analyze the data through SPSS version 25. The study revealed significant influence of image of entrepreneurship on developing entrepreneurial inclination among management students. However, study resulted no significant influence of entrepreneurial course and content and role models on developing entrepreneurial inclination. These results suggest that management students have a positive perception of entrepreneurship, which plays a crucial role in fostering their intention to become entrepreneurs. The curriculum and content as well as role models fail to inspire students toward entrepreneurial activities or provide real-life simulations of the entrepreneurial process. This results suggest that the academic institutions should make effort on aligning the theoretical course with practical approach as well as should conduct the various support program that encourage students to adopt entrepreneurial career and develop networking approach to real world entrepreneurs.